Der Professorenroman : Michel Zink entre philologie et invention - Monica Longobardi (Revue des Langues Romanes)
The present research intends to investigate the links between the institutional activity of the famous medievalist, Michel Zink, and three of his less well-known novels (at least in Italy): the novel about the grail “Déodat ou la transparence” (2002); the volume in the investigative series “Arsène Lupin et l’affaire d'Arsonval” (2004) and the satirical novel “Un portefeuille toulousain” (2007). Beyond differences in the literary genre, many more or less evident cases of intertextuality reveal surprising contacts between the Romance literature of the Middle Ages, the savants who practise it by profession, and the novels which, the fruit of the same author, borrow many scholarly themes.